Real-time contingency evaluation and ranking technique - Moghavvemi, M.; Faruque, O. (IEE Proceedings, 1998)
The tendency towards maximising economic benefits has led power systems utilities to run close to the limits of stable operation. This has necessitated the study of the stressed situation of the power system network to accomplish efficient energy management without losing its reliability. On-line monitoring of power system stability has become a vital factor for electric utilities. An effective method for real-time monitoring of system status and thus voltage collapse prediction is described. The proposed technique investigates each line of the system through calculating an indicator that varies from 0 (no load condition) to 1 (maximum permissible loading condition). The basic concept of maximum power transfer through a line is utilised. The proposed contingency evaluation technique is applied on the IEEE 24 bus and IEEE 6 bus reliability test system and is found to be accurate in assessing the stressful status of the lines.